COMPARISON OF DIFFERENT THERAPUTIC TECHINQUES ON HAMSTRING FLEXBILITY IN NORMAL ADULTS: RANDOMIZED CONTROLLED TRIAL (International Journal of Physiotherapy, 2016)
Background: Hamstring muscles involve a rate of intense musculoskeletal injuries. Hamstring flexibility, shorting, and exhaustion are hazard variables connected with hamstring strain. Enhanced flexibility has for quite some time been viewed as an imperative part in anticipation of musculotendinous strain. Expanding hamstring flexibility can assume a vital part in counteracting lower furthest point injuries. In any case, few research has been performed on the best technique. This study was conducted to correlate the effect of different therapeutic techniques (active release, muscle energy and Mulligan) on increasing hamstring flexibility.Methods: Fifty seven normal healthy male subjects with hamstring tightness were assigned randomly to one of the four study groups: Group (1)13subjects received active release technique. Group (2)15subjects received muscle energy technique. Group (3) 12subjects received Mulligan’s technique. Group (4)17subjects did not get any intercession. Popliteal angle (active knee extension test) and sit-reach flexibility test were measured pre and post the intervention period.Results: MANOVA test for active knee extension test and sit-reach test among the four groups for post intervention values there was no significant difference between Group 1 and Group 2 in the post values of AKE with both groups showed significant increases than Group 3. Group 1 versus Group 3: p < 0.0001, CI: 3.5-11.8; Group 2 versus Group 3: p < 0.0001, CI: 4.6-12.8).Conclusion: It can be reasoned that both active release and muscle energy techniques have similar impact in enhancing hamstring flexibility than Mulligan technique in normal male adults.